Two new species and a new synonym of the genus Paederus Fabricius (Coleoptera: Staphylinidae: Paederinae) from China - Li, Xiao-Yan; Solodovnikov, Alexey; Zhou, Hong-Zhang (Zootaxa, 2014)
Two new species of the genus Paederus Fabricius, 1775 from mainland China are described: Paederus (Harpopaederus) brevior sp. nov. (Shaanxi) and P. (H.) multidenticulatus sp. nov. (Hubei). One new synonym is proposed: Paederus parvidenticulatus Li, Zhou & Solodovnikov, 2013 = Paederus symmetricus Li, Zhou & Solodovnikov, 2013 syn. nov.